VARIASI PENDEKATAN KULIAH TATAP MUKA DALAM KAITAN DENGAN PEMAHAMAN STUDENT CENTERED LEARNING - Rhendy Wijayanto (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2016)
ABSTRACT Lecture is the most common instruction method used. In order to be effective, it has to be arranged so that students are not merely passive receiver, but an active learner and contributor.  In giving lecture, lecture is responsible to pack information so that it becomes simple and understandable.  Lecture benefits from its ability to squeeze abundant information and delivered to a bunch of students.  Lecture contains: introduction, content, and closing.  There are some method to make lecture interesting without interfering the core content such as: short breaks during lecture, premeditated question to enhance active thinking, and test at the end of lecture to help understanding information.  There are several types of lecture based on its context such as: Oral presentation, Visual information giver, Exemplary performer, Eclectic lecturer,  and Amorphous talker. Meanwhile from structure point of view, there are five types: classical, problem based, sequential, comparative, and thesis type. In giving good lecture, there are several essential skills which is important to be mastered to support lecture such as: prepoaration, opening, explanation, information description, narration, comparison, audio visual, student response, student activity, and summary.  The discussion is integrated into an observed case study to facilitate understanding. Keyword: Lecture, interactive, PBL, student centered